MRI Evaluation using DWI and T2WI of Residual Lymph Nodes in patients Affected by Head and Neck Squamous Cell Carcinoma Treated with Chemo-radiotherapy - Piludu, Francesca; Gangemi, Emma; Marucci, Laura; Guerrisi, Antonino; Pellini, Raul; Covello, Renato; Carlini, Paolo; Spriano, Giuseppe; Sanguineti, Giuseppe; Marzi, Simona; Vidiri, Antonello (Current Medical Imaging, 2018)
Objective: the purpose of this study was to assess residual neck nodes after Chemo- Radiotherapy (CRT) using diffusion and T2 weighted imaging. Methods: Apparent Diffusion Coefficient (ADC) and T2 signal intensity were retrospectively analyzed in 45 residual nodes 8 weeks after the end of CRT. Sensitivity, specificity, Positive and Negative Predictive Values (PPV, NPV) and accuracy of diffusion and T2 weighted sequences were calculated. In a subgroup of 25 patients ADC and T2 signal intensity were compared to Positron Emission Tomography - Computed Tomography (PET-CT) results. Histopathology and a 24 months follow- up after CRT were used as reference standard. Results: T2 signal intensity showed an accuracy of 63%, a sensitivity of 73.3%, a specificity of 55.6%, a PPV of 53.8% and a NPV of 75%. ADC showed an accuracy of 71.1%, using a threshold of 1.25 10-3 mm2/s, a sensitivity of 52.6%, a specificity of 84.6%, a PPV of 71.4% and a NPV of 71%. The combination of T2 signal intensity and ADC showed an accuracy of 73.3%, a sensitivity of 50%, a specificity of 84.6%, a PPV of 60% and a NPV of 78.7%. In the subset of 25 patients we correlated ADC and T2 data with PET-CT data: the latter showed higher accuracy, sensitivity and NPV and lower specificity; the PPV was similar between the two methods. Conclusion: Our results demonstrated that MRI, using diffusion and T2 weighted imaging, has high specificity in detecting post-CRT residual neck nodes but it has a lower accuracy, sensitivity and NPV than PET-CT.
Keywords: Lymph nodes